A simple method of fast evaluating full-field wake velocities for arbitrary wind turbine arrays on complex terrains. (December 2022) - Liu, Haixiao; Fu, Jianing; Liang, Zetao; Liang, Zhichang; Zhang, Yuming; Xiao, Zhong
Abstract: Wind energy is an important option of renewable energy and plays more and more an irreplaceable role in many regions. A technical and meanwhile a scientific problem directly relevant to selecting the wind farm site, optimizing the wind farm layout and evaluating the power output, is to calculate accurately the wake effects generated behind wind turbines, which affect the wind velocity distribution of downstream turbines and reduce the power output of a wind farm. Through modifications of near-field and far-field empirical wake models and the wake model on a complex terrain, a unified wake model is developed to calculate the full-field wake velocity distribution over a wind farm with arbitrary turbine arrays located on flat or complex terrains. The derived wake velocity is formulated in an explicit and concise form to obtain the wind velocity at any position within the turbine arrays. The velocity distribution over the whole array can be fast acquired by implementing a simple procedure and occupying the least computing resources. Compared to the CFD modelling, the present method performs superiorly in both easiness and efficiency, which would be a powerful tool in designing and optimizing a large wind farm composed of numerous and variably deployed turbines of different densities on complex terrains. With this solution, it becomes feasible to construct the wind turbine arrays at the sites of restricted space, specifically the offshore islands and the large floating structures.